Validation of an unstructured CFD solver for complete helicopter configurations with loose CSD-trim coupling - Wendlisch, J.H.; Raddatz, J. (My University, 2014)
The present study addresses the applicability of the unstructured CFD solver TAU of the German Aerospace Center (DLR) for the simulation of isolated rotors and complete helicopter configurations. Rotor trim and elasticity of the rotorblades is taken into account by loose fluid-structure-trim coupling. Numerical results are presented and compared to experimental measurements of the GOAHEAD windtunnel campaign. The selected testcase of the GOAHEAD experimental database corresponds to a cruise flight condition at Ma=0.204 with an advance-ratio of µ = 0:33. Validation results for the isolated mainrotor are in excellent agreement with CFD reference solutions and in good agreement with experimental data. CFD simulation for the rotor-fuselage configuration shows a good correlation with experimental data.